Three-dimensional lower-limb kinematics during undulatory underwater swimming - Matsuda, Y.; Kaneko, M.; Sakurai, Y.; Akashi, K.; Yasuo, S. (Sports Biomechanics, 2021)
The three-dimensional (3D) motion of lower-limb joints is evaluated during various sports. However, few studies have reported the 3D lower-limb joint movement during undulatory underwater swimming (UUS). This study aimed to investigate the relationship between 3D lower-limb kinematics and forward-swimming velocity during UUS at maximal velocity. A total of 26 male international- and national-level swimmers were assessed during UUS using a motion-capture system. The 3D angle and angular velocity of the lower-limb joints were calculated and relationships between forward-swimming velocity, angle, and angular velocity were investigated using correlation analysis. The peak angular velocities of hip internal and external rotation were significantly correlated with forward-swimming velocity (r = .48, p = .01 and r =-.74, p < .01, respectively). Peak hip internal rotation was observed at the middle of down-kicking (25% kick cycle, 243 °/s), whereas peak external rotation was observed at the terminal of down-kicking (50% kick cycle, -351 °/s). The swimmers showed a higher peak angular velocity of hip internal/external rotation with a large active range of motion for hip rotation. The swimmers moved their lower-limb joints three-dimensionally, and aside from flexion/extension movements, and hip rotation may increase UUS proficiency.